Food insecurity a reference handbook - Schanbacher, William D.; Uy, Whitney Fung (Contemporary world issues, 2023)
"This comprehensive and authoritative all-in-one resource examines the issue of food insecurity in the United States, including the various economic, social, political, and cultural factors that drive the problem"--